Live birth after cervical ectopic uterus transplantation in mice. Issue 8 (14th March 2020) - Yu, Shengnan; Xie, Baiyi; Zhang, Liyi; Song, Youyi; Yang, Ying; An, Ke; Huang, Xiumin; Qi, Zhongquan; Xia, Junjie
Abstract : An ideal animal model is a prerequisite for the basic research of uterus transplantation. This study aimed to develop a new cervical ectopic uterus transplantation mice model, which was established by vascular anastomosis of the right common iliac artery and vein of the donor with the right common carotid artery and external jugular vein of the recipient, respectively, using the cuff method. The survival status of the transplanted uterus was assessed by macroscopic observation and histological examination after surgery, and the function of the graft uterus was tested by verifying whether the pregnancy is possible. A total of 40 transplants were performed, of which only 1 failed due to donor hemorrhage. After 26 transplants, the total operation time reduced to 52.4 ± 3.8 minutes, of which the total ischemia time took 6.6 ± 1.1 minutes. Sixty days after transplantation, all the graft uteri had a good blood supply and spontaneous contraction. The histology showed no significant difference between the transplanted uterus and the native. Embryo transfer experiments have proven that the transplanted uterus has uterine function. In conclusion, this new model is an effective and simple mice model for the studies of the scientific issues related to uterus transplantation. Abstract : The cervical ectopic uterus transplantation mouse model is an effective tool for the basic research of uterus transplantation.